2015
DOI: 10.1523/jneurosci.3795-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Activity in Human Visual and Parietal Cortex Reveals Object-Based Attention in Working Memory

Abstract: Visual attention enables observers to select behaviorally relevant information based on spatial locations, features, or objects. Attentional selection is not limited to physically present visual information, but can also operate on internal representations maintained in working memory (WM) in service of higher-order cognition. However, only little is known about whether attention to WM contents follows the same principles as attention to sensory stimuli. To address this question, we investigated in humans whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 54 publications
8
32
0
3
Order By: Relevance
“…It has remained less clear if working memory also relies on persistent activity in early visual cortical areas12. On the one hand, fMRI studies in humans reveal signatures of the items in working memory in higher but also in lower visual areas74749. Indeed, it is possible to decode the stimulus in memory from early visual areas by analysing the pattern of the fMRI signal across multiple voxels1550, even when the visually driven fMRI response has decayed back to baseline5152.…”
Section: Discussionmentioning
confidence: 99%
“…It has remained less clear if working memory also relies on persistent activity in early visual cortical areas12. On the one hand, fMRI studies in humans reveal signatures of the items in working memory in higher but also in lower visual areas74749. Indeed, it is possible to decode the stimulus in memory from early visual areas by analysing the pattern of the fMRI signal across multiple voxels1550, even when the visually driven fMRI response has decayed back to baseline5152.…”
Section: Discussionmentioning
confidence: 99%
“…Hemispheric asymmetries supporting an inter-hemispheric competition in attentional control were also observed, since only the right SPL-1 and left IPS-2 (with FEF) generate contralateral attention signals stronger than their contralateral corresponding regions. In some of these topographic maps, priority shapes the activation profile (Jerde et al, 2012) along a rostrocaudal and inferior-superior gradient representing maintenance of saccade planning, covert attention, and working memory (see also Peters et al, 2015), and defines prioritized maps of space. These maps can be modulated by reward-based mechanisms (Chelazzi et al, 2014).…”
Section: The Superior Parietal Lobule and The Intraparietal Sulcusmentioning
confidence: 99%
“…For example, both behavioral and neuroimaging studies have shown that spatial attention can also be directed to internally stored locations (Awh, Jonides, & Reuter-Lorenz, 1998) and that attentional shifts in perception and WM involve similar brain regions (Bledowski, Rahm, & Rowe, 2009;Nobre et al, 2004). Recently, we have demonstrated that also the principle of objectbased attention is used in WM (Peters, Kaiser, Rahm, & Bledowski, 2015) by adapting the perceptual paradigm of Egly et al (Egly et al, 1994) to WM. Participants had to memorize the exact location of two objects' endpoints which changed their position across trials.…”
mentioning
confidence: 99%
“…Until now, it has remained unclear whether attentional sampling is specific to the selection of perceptual information or whether it constitutes a more general mechanism of information processing in human cognition. Based on the findings of rhythmic fluctuations of object-based attention in a perceptual paradigm (Fiebelkorn et al, 2013) and object-based attention effects in WM (Peters et al, 2015), the present study assessed whether attentional sampling also operates on information that is not externally present but represented internally, in WM. We employed a variant of our previous paradigm (Peters et al, 2015) and varied the interval between attentional cue and probe with a high temporal resolution to study the temporal trajectory of object-based attention in WM.…”
mentioning
confidence: 99%